2012
DOI: 10.1038/cdd.2012.102
|View full text |Cite
|
Sign up to set email alerts
|

The critical role of catalase in prooxidant and antioxidant function of p53

Abstract: The tumor suppressor p53 is an important regulator of intracellular reactive oxygen species (ROS) levels, although downstream mediators of p53 remain to be elucidated. Here, we show that p53 and its downstream targets, p53-inducible ribonucleotide reductase (p53R2) and p53-inducible gene 3 (PIG3), physically and functionally interact with catalase for efficient regulation of intracellular ROS, depending on stress intensity. Under physiological conditions, the antioxidant functions of p53 are mediated by p53R2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(71 citation statements)
references
References 41 publications
(51 reference statements)
2
57
1
2
Order By: Relevance
“…On that account, inhibition of the mTOR pathway not only downregulated the expression of p53 but also attenuated the downstream signaling and the outcome of the p53 activation. p53 has been reported to be the modulator of oxidative stress-it downregulates low oxidative stress and exacerbates higher levels of stresses (22). For example, at low levels of oxidative stress, p53 activates antioxidant genes such as sestrin and glutathione peroxidase (1,6,16).…”
Section: Discussionmentioning
confidence: 99%
“…On that account, inhibition of the mTOR pathway not only downregulated the expression of p53 but also attenuated the downstream signaling and the outcome of the p53 activation. p53 has been reported to be the modulator of oxidative stress-it downregulates low oxidative stress and exacerbates higher levels of stresses (22). For example, at low levels of oxidative stress, p53 activates antioxidant genes such as sestrin and glutathione peroxidase (1,6,16).…”
Section: Discussionmentioning
confidence: 99%
“…5) is also consistent with the hypothesis that these antioxidant enzymes are mechanistically involved in the crossroads of Cl-amidine and its ability to suppress an oxidative burst. Because Cl-amidine induces p53 Cui et al, 2013) and p53 drives the expression of antioxidant enzymes (Tan et al, 1999;Hussain et al, 2004;Yoon et al, 2004;Bensaad et al, 2006;Popowich et al, 2010;Kang et al, 2013), potentially p53 repression by PADs (either by direct or upstream citrullination) is suppressing the ability of p53 to activate antioxidant enzymes. This hypothesis, though, would have to be tested.…”
Section: Discussionmentioning
confidence: 99%
“…Evidences have shown that p53 possesses potent redox-regulating activity through regulating various ROS-generating and antioxidant enzymes. [27][28][29] Increasing cellular ROS promotes p53 expression which induces pro-oxidant genes resulting in cell death. However, other studies report that p53 is associated with the expression of antioxidant genes such as GPx and SOD, showing that p53 also has a protective function and is involved in antioxidant defense system.…”
Section: Effect Of Gallic Acid and Dodecyl Gallate Against Acutementioning
confidence: 99%